Characterization of Secondary Metabolites, Biological Activity and Glandular Trichomes of Stachys tymphaeaHausskn. from the Monti Sibillini National Park (Central Apennines, Italy). Issue 2 (February 2014) - Venditti, Alessandro; Bianco, Armandodoriano; Nicoletti, Marcello; Quassinti, Luana; Bramucci, Massimo; Lupidi, Giulio; Vitali, Luca Agostino; Papa, Fabrizio; Vittori, Sauro; Petrelli, Dezemona; Maleci Bini, Laura; Giuliani, Claudia; et al.
Abstract Stachys tymphaea (Lamiaceae) is a perennial herb growing in forest openings and dry meadows of central and southern Italy. It was investigated for the first time here, determining the content of secondary metabolites, the micromorphology of glandular trichomes, the histochemical localization of secretion, and the biological activity of the volatile oil, namely, the cytotoxic, antioxidant, and antimicrobial properties. The plant showed a peculiar molecular pattern, being rich of biophenolic compounds as flavonoids, phenylethanoid glycosides, and caffeoylquinic acid derivatives, but poor of iridoids, which are known as marker compounds of the genus Stachys. The essential oil was characterized by GC‐FID and GC/MS analyses, revealing a high percentage of sesquiterpene hydrocarbons (54.6%), with germacrene D (30.0%) and (E)‐β‐farnesene (12.4%) as the most abundant compounds, while other main components were representatives of the diterpenes (19.2%), represented mainly by (E)‐phytol (11.9%). This composition supported the taxonomic relationships in the genus Stachys, which comprises oil‐poor species producing essential oils rich in hydrocarbons, with germacrene D as one of the predominant components. The micromorphological study revealed three types of glandular hairs, i.e., Type A peltate trichomes, being the primary sites of essential oil biosynthesis, Type B short‐stalked trichomes, typical mucopolysaccharide producers, and Type C long capitate trichomes, secreting a complex mixture of both lipophilic and hydrophilic substances, with a major phenolic fraction. Moreover, the MTT assay revealed the potential of the volatile oil to inhibit A375, HCT116, and MDA‐MB 231 tumor cells lines (IC50 values of 23.9–34.4 μg/ml).